Transfer And Terminations As Staffing Options - Heizer, Jay (Academy of Management Journal, 1976)
The article presents the findings of studies on staffing, transfer and termination in organizational management. Two hundred and ninety critical incidents were gathered from production and purchasing supervisors. The incidents were evaluated by the author and an independent judge to determine which incidents included staffing. Incidents which included staffing as manager actions contributing to effective and ineffective incidents are tabulated. The possibility exists that the concern associated with terminations and transfers was such as to make the incidents vivid in the memory of the respondents.